Motor Skills of Children and Adolescents Are Influenced by Growing up Barefoot or Shod - Zech, Astrid; Venter, Ranel; de Villiers, Johanna E.; Sehner, Susanne; Wegscheider, Karl; Hollander, Karsten (Frontiers in Pediatrics, 2018)
Background: The objective of this study was to evaluate the association between growing up barefoot or shod and the development of motor performance during childhood and adolescence. Methods: Habitual barefoot and shod children and adolescents between 6 and 18 years were recruited in South Africa and Germany. Participants completed balance, standing long jump and 20m sprint tests in barefoot and shod conditions. Outcomes were analysed in separate mixed-effects linear regressions for three age groups according to stages of development (6 to 10 years, 11 to 14 years, 15 to 18 years). All models were adjusted for confounders: gender, ethnicity, BMI, PAQ score and order of tests (barefoot vs. shod). Results: 385 habitually barefoot and 425 habitually shod children participated. Significant age by footwear effects were found for the jump (p=0.032) and sprint test (p=0.041). Habitually barefoot children aged 6 to 10 years scored higher in the balance test (p=0.015) and standing long jump (p=0.005) whereas shod children sprinted faster (p<0.001). Faster sprint times were found for habitually shod participants between 11 to 14 years (p<0.001). Barefoot adolescents between 15 to 18 years of age showed a greater long jump distance (p<0.001) but slower sprint times (p=0.014) than shod adolescents. Conclusions: The results emphasize the importance of footwear habits for the development of motor skills during childhood and adolescence. Regular physical activities without footwear may be beneficial for the development of jumping and balance skills, especially in the age of 6 to 10 years.